Some legal issues for Vietnam on workers' right to organize in the new generation of free trade agreements - Truong, Chanh Duc (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
In recent years, Vietnam has achieved many significant achievements in economic development through promoting openness, integration into the global economy, and actively participating in the new generation of free trade agreements. Vietnam has participated in negotiations and signed 16 Free Trade Agreements (FTA), among which the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) and the European Union-Vietnam Free Trade Agreement (EVFTA) are two "new generation" free trade agreements with many new commitments on labor, including the right to freedom of association of workers in enterprises. This article focuses on clarifying the provisions on the right to establish representative organizations of workers in the CPTPP and EVFTA, as well as the challenges that Vietnam must face in amending and supplementing the legal provisions to implement these agreements effectively.